Enhancing solid-state hydrogen storage via integrating helical coil heat exchanger with sandwiched phase change materials - Puyang Lu; Mingjie Lai; Rui Zhou; Zhuofan Chen; Haichen Yao; Zhi Li; Fanjun Deng; Xianglei Liu (Fuel, 2027)

Mechanisms underlying the antifungal activity of diethylthiosulfinate against marrow squash wet rot caused by Fusarium solani - Chenxia Liu; Jinglin Zhang; Hui He; Qiankun Wang; Fanjun Kong; Chunfang Wang; Longshen Wang; Xiao Wang; Bingjie Chen; Yuemei Zhang; Junfeng Liu; Yongxing Gu; et al. (International Journal of Food Microbiology, 2026)

Enzyme-assisted extraction of proteins from radish leaf and their structure-function relationship in stabilizing high internal phase emulsions compared to soy protein and whey protein - Hang Wang; Fanjun Meng; Yinghan Zhao; Yang Liu; Jian Chen; Xiao Liu (Food Hydrocolloids, 2025)

Improving storage stability of dairy emulsions via xanthan gum and carboxymethyl cellulose synergy - Qingyun Xu; Jiaming Li; Fanjun Meng; Yanfang Sun; Xuexian Du; Yingle Wu; Jianguo Yan; Jian Chen; Anqi Chen; Jianghua Li (Food Bioscience, 2025)

Allicin derivative (DETS) treatment reduced post-harvest decay in strawberries by inhibiting Botrytis cinerea viability and increasing antioxidant capacity - Chenxia Liu; Fanjun Kong; Yongjin Qiao; Hui He; Chunfang Wang; Qiankun Wang; Xiao Wang; Bingjie Chen; Liqiong Zhang; Wei Xiao; Huali Lin; Biao Jiang; et al. (Food Control, 2025)

An Exploratory Assessment of a Submarine Topographic Characteristic Index for Predicting Extreme Flow Velocities: A Case Study of Typhoon In−Fa in the Zhoushan Sea Area - Fanjun Chen; Wankang Yang; Long Xiao; Xiaoliang Xia; Kaixuan Ding; Zhilin Sun (Journal of Marine Science and Engineering, 2025)
This study analyzes the 96 h flow velocity time series data from the Zhoushan Sea during Typhoon In−fa to investigate the conditions for extreme flow velocities. Through force analysis of the unit fluid and statistical analysis of topographic features, we identified the critical water depth, slope, and sea surface width for extreme flow velocities under ideal conditions as 15 m, 4.5°, and 2000 m, respectively. The Submarine Topographic Characteristic Index (STCI) is introduced for the first time in this study, revealing its significant impact on extreme flow velocities. Three types of “extreme velocity points”—associated with constant storm surge, astronomical tide, and typhoon storm surge—were defined, occurring over 85% of the time during typhoon events. These extreme velocity points were analyzed in relation to their topographic characteristics, including water depth, slope, and sea surface width. Simulations of Typhoon In−fa in the Zhoushan Sea area were used to construct the STCI model, resulting in the following weightings: water depth = 0.96, slope = 0.39, and sea surface width = 0.49. Typhoon In−fa occurred in 2021, exhibited a maximum wind speed of approximately 35 m/s, and played a key role in the hydrodynamic processes investigated in this study. Validation with Typhoons Muifa (2021) and Bebinca (2413) confirmed the model’s high consistency. The STCI model provides insight into the occurrence of extreme velocities, categorizing them according to tidal phase and typhoon influence. Preliminary findings indicate the model’s applicability under varying typhoon intensities, offering a robust tool for predicting extreme seabed flow velocities during typhoon events.

Effect of Nonlinear Factors on Typhoon-Induced Storm Surges - Fanjun Chen; Kaixuan Ding; Zhilin Sun (Journal of Marine Science and Engineering, 2024)
This study employs the Delft3D numerical model to elucidate nonlinear interactions in velocity dynamics across four key marine regions during typhoon-induced storm surges (Typhoon In-fa, No. 2106). To address gaps in understanding how typhoon winds drive storm surges, this study aims to analyze the relative contributions of bottom friction, wind stress, and convective terms to storm surge dynamics, providing insights for predictive modeling and marine hazard mitigation. Introducing a novel metric, the “Flow Velocity Nonlinear Coupling Proportion” (“FVNCP”, abbreviated as “NCP”), this research quantifies the interactive effects of storm surge flow velocity by dissecting the contributions of bottom friction, wind stress, and the convective term. Through decision tree modeling, wind stress emerges as the primary driver of NCP in open sea and sheltered areas, with peak values reaching 1.50 × 10−4 and 2.14 × 10−4 m/s2, respectively. In contrast, the convective term dominates the strait and bypassing regions, exhibiting maximum impacts of 3.21 × 10−4 and 2.94 × 10−4 m/s2, while bottom friction’s influence is consistently minor across all regions. Wind stress contributes the most to NCP in open waters, at an average of 48.28%, while the convective term exerts a comparable 38.85% effect. In confined areas like the strait and bypassing regions, the convective term accounts for 40–44% of the NCP, with wind stress contributing 32–39%. The role of bottom friction is the least among the three factors though its impact intensifies in shallower zones. These findings offer critical insights for advancing predictive models and informing strategies to mitigate typhoon-driven marine hazards.

Genomic basis determining root system architecture in maize - Pengcheng Li; Zhihai Zhang; Gui Xiao; Zheng Zhao; Kunhui He; Xiaohong Yang; Qingchun Pan; Guohua Mi; Zhongtao Jia; Jianbing Yan; Fanjun Chen; Lixing Yuan (Theoretical and Applied Genetics, 2024)

Three-Dimensional Turbulent Simulation of Bivariate Normal Distribution Protection Device - Jing Liu; Zongyu Li; Hanming Huang; Weiwei Lin; Zhilin Sun; Fanjun Chen (Journal of Marine Science and Engineering, 2024)
In response to the deficiencies in existing bridge pier scour protection technologies, this paper introduces a novel protective device, namely a normal distribution-shaped surface (BND) protection devices formed by rotating a concave normal curve. A three-dimensional turbulent SST k−ω model is constructed, and physical model experiments of conical surfaces are conducted to validate the mathematical model. The simulation analyzes longitudinal water flow, downflow, vorticity intensity, and shear stress within normal and conical surfaces. The results show that the downflow distribution in front of the pier spans a relative water depth of (−0.45, 0.67), with a peak velocity approximately 70% of the longitudinal flow velocity. Circulation forms within the surfaces, with the main vortex flux inside the BND being 33% lower than that inside the conical surface. The maximum shear stress coefficient inside the BND can reach 9, and the protective surface isolates the bed from the flow to prevent scouring by high shear stress. The velocity gradient at the edge of the surface is small, and the edge shear stress of the 3D normal distribution-shaped surface (BND) protection device is only one-third of that of the conical surface, preventing edge scouring. The large shear stress and its distribution area decrease monotonically with the increase in surface width. When the surface width is four times the diameter, the distribution range of the shear stress coefficient greater than 1 is very small. The study of three-Dimensional turbulence within the BND provides a numerical basis for an anti-scour design.

Char and soot records of the Holocene fire history and its implications for climate-vegetation change and human activities within the Guanzhong Basin, southern Loess Plateau, China - Yuzhu Zhang; Qili Xiao; Yan Zhu; Ninglian Wang; Menglei Wu; Yanfeng Li; Jianxi Li; Dou Chen; Xiaoling Huang; Sikai Wang; Pengpeng Cao; Yao Jin; et al. (Science of The Total Environment, 2024)

Root growth, root senescence and root system architecture in maize under conservative strip tillage system - Ye Sha; Zheng Liu; Zhanhong Hao; Yiwen Huang; Hui Shao; Guozhong Feng; Fanjun Chen; Guohua Mi (Plant and Soil, 2024)

A photo-triggered coating of prosthetic valve leaflet surface to realize antibacterial and thrombolysis on-demand - Yuan Wei; Xiangling Fan; Jingze Liu; Chong Chen; Ruiqi Dong; Hao Zhang; Li Yang; Rifang Luo; Fanjun Zhang; Yunbing Wang (Chemical Engineering Journal, 2024)

Development of injectable hyaluronic acid-based hydrogels with antioxidant activity for the treatment of corneal neovascularization - Linyu Long; Zhengwei Ge; Fanjun Zhang; Ruiqi Dong; Li Yang; Zhongping Chen; Shibo Tang; Yunbing Wang (Chemical Engineering Journal, 2023)

An analytic model of typhoon wind field and simulation of storm tides - Zhilin Sun; Kaixuan Ding; Zongyu Li; Fanjun Chen; Shanhong Zhong (Frontiers in Marine Science, 2023)
Storm tides have intensified due to global climate warming, with limited attention given to storm current velocity (SCV) due to data scarcity during hurricanes/typhoons and limitations in existing wind models’ accuracy. We propose an analytic model incorporating sea-surface resistance into the gradient wind equation, offering a theoretically robust approach. Through rigorous verification against measured data, our model demonstrates significant accuracy improvement compared to established models. Simulating storm tides during Typhoon Rammasun using our approach reveals strong agreement between calculated SCVs and measured data, surpassing the performance of the Holland model. Notably, typhoon storm surges primarily respond to pressure, while SCVs are predominantly governed by wind speed in open sea. The highest water level aligns with the lowest pressure, with maximum SCVs trailing the maximum wind radius. SCVs significantly exceed astronomical tidal current velocities (ACVs) in the open sea, reaching a maximum of 3.57 m/s. Areas where the SCV-to-ACV ratio exceeds 3 constitute 21.4% of the study area. Combining our wind model with Typhoon SCV simulations provides valuable insights into storm tide dynamics, advancing our understanding of storm tide mechanisms and informing mitigation strategies.

Hybrid performance evaluation and genome-wide association analysis of root system architecture in a maize association population - Zhigang Liu; Pengcheng Li; Wei Ren; Zhe Chen; Toluwase Olukayode; Guohua Mi; Lixing Yuan; Fanjun Chen; Qingchun Pan (Theoretical and Applied Genetics, 2023)

Plasma cell-free DNA promise monitoring and tissue injury assessment of COVID-19 - Xin Jin; Yanqun Wang; Jinjin Xu; Yimin Li; Fanjun Cheng; Yuxue Luo; Haibo Zhou; Shanwen Lin; Fei Xiao; Lu Zhang; Yu Lin; Zhaoyong Zhang; et al. (Molecular Genetics and Genomics, 2023)
Coronavirus 2019 (COVID-19) is a complex disease that affects billions of people worldwide. Currently, effective etiological treatment of COVID-19 is still lacking; COVID-19 also causes damages to various organs that affects therapeutics and mortality of the patients. Surveillance of the treatment responses and organ injury assessment of COVID-19 patients are of high clinical value. In this study, we investigated the characteristic fragmentation patterns and explored the potential in tissue injury assessment of plasma cell-free DNA in COVID-19 patients. Through recruitment of 37 COVID-19 patients, 32 controls and analysis of 208 blood samples upon diagnosis and during treatment, we report gross abnormalities in cfDNA of COVID-19 patients, including elevated GC content, altered molecule size and end motif patterns. More importantly, such cfDNA fragmentation characteristics reflect patient-specific physiological changes during treatment. Further analysis on cfDNA tissue-of-origin tracing reveals frequent tissue injuries in COVID-19 patients, which is supported by clinical diagnoses. Hence, our work demonstrates and extends the translational merit of cfDNA fragmentation pattern as valuable analyte for effective treatment monitoring, as well as tissue injury assessment in COVID-19.

Mining genes regulating root system architecture in maize based on data integration analysis - Kunhui He; Zheng Zhao; Wei Ren; Zhe Chen; Limei Chen; Fanjun Chen; Guohua Mi; Qingchun Pan; Lixing Yuan (Theoretical and Applied Genetics, 2023)

Nitrogen responsiveness of leaf growth, radiation use efficiency and grain yield of maize (Zea mays L.) in Northeast China - Zheng Liu; Jia Gao; Siyu Zhao; Ye Sha; Yiwen Huang; Zhanhong Hao; Lihua Ke; Fanjun Chen; Lixing Yuan; Guohua Mi (Field Crops Research, 2023)

Dissecting the phenotypic response of maize to low phosphorus soils by field screening of a large diversity panel - Dongdong Li; Zhe Chen; Meng Wang; Willmar L. Leiser; Thea Mi Weiß; Zheng Zhao; Song Cheng; Shaojiang Chen; Fanjun Chen; Lixing Yuan; Tobias Würschum; Wenxin Liu (Euphytica, 2021)

The physiological mechanism underlying root elongation in response to nitrogen deficiency in crop plants - Xichao Sun; Fanjun Chen; Lixing Yuan; Guohua Mi (Planta, 2020)

Soil plant-available phosphorus levels and maize genotypes determine the phosphorus acquisition efficiency and contribution of mycorrhizal pathway - Qun Chu; Lin Zhang; Jianwei Zhou; Lixing Yuan; Fanjun Chen; Fusuo Zhang; Gu Feng; Zed Rengel (Plant and Soil, 2020)

Glutamine application promotes nitrogen and biomass accumulation in the shoot of seedlings of the maize hybrid ZD958 - Mahmood Ul Hassan; Md Monirul Islam; Ruifeng Wang; Jingyu Guo; Huilan Luo; Fanjun Chen; Xuexian Li (Planta, 2020)

Genotypic difference in the plasticity of root system architecture of field-grown maize in response to plant density - Hui Shao; Dongfeng Shi; Wenjun Shi; Xiangben Ban; Yachao Chen; Wei Ren; Fanjun Chen; Guohua Mi (Plant and Soil, 2019)

Root growth and root system architecture of field-grown maize in response to high planting density - Hui Shao; Tingting Xia; Dali Wu; Fanjun Chen; Guohua Mi (Plant and Soil, 2018)

Overexpression of the maize ZmAMT1;1a gene enhances root ammonium uptake efficiency under low ammonium nutrition - Yang Zhao; Zhi Liu; Fengying Duan; Xia An; Xiangguo Liu; Dongyun Hao; Riliang Gu; Zhangkui Wang; Fanjun Chen; Lixing Yuan (Plant Biotechnology Reports, 2018)

ZD958 is a low-nitrogen-efficient maize hybrid at the seedling stage among five maize and two teosinte lines - Jienan Han; Lifeng Wang; Hongyan Zheng; Xiaoying Pan; Huiyong Li; Fanjun Chen; Xuexian Li (Planta, 2015)

Comprehensive phenotypic analysis and quantitative trait locus identification for grain mineral concentration, content, and yield in maize (Zea mays L.) - Riliang Gu; Fanjun Chen; Bingran Liu; Xin Wang; Jianchao Liu; Pengcheng Li; Qingchun Pan; Jordon Pace; Ayaz-Ali Soomro; Thomas Lübberstedt; Guohua Mi; Lixing Yuan (Theoretical and Applied Genetics, 2015)

Changes in root size and distribution in relation to nitrogen accumulation during maize breeding in China - Xiaochao Chen; Jie Zhang; Yanling Chen; Qian Li; Fanjun Chen; Lixing Yuan; Guohua Mi (Plant and Soil, 2014)

Mycorrhizal responsiveness of maize (Zea mays L.) genotypes as related to releasing date and available P content in soil - Qun Chu; Xinxin Wang; Yang Yang; Fanjun Chen; Fusuo Zhang; Gu Feng (Mycorrhiza, 2013)

Evaluation of the yield and nitrogen use efficiency of the dominant maize hybrids grown in North and Northeast China - FanJun Chen; ZenGuo Fang; Qiang Gao; YouLiang Ye; LiangLiang Jia; LiXing Yuan; GuoHua Mi; FuSuo Zhang (Science China Life Sciences, 2013)

Modern maize hybrids in N ortheast C hina exhibit increased yield potential and resource use efficiency despite adverse climate change - Xiaochao Chen; Fanjun Chen; Yanling Chen; Qiang Gao; Xiaoli Yang; Lixing Yuan; Fusuo Zhang; Guohua Mi (Global Change Biology, 2013)
The impact of global changes on food security is of serious concern. Breeding novel crop cultivars adaptable to climate change is one potential solution, but this approach requires an understanding of complex adaptive traits for climate‐change conditions. In this study, plant growth, nitrogen (N) uptake, and yield in relation to climatic resource use efficiency of nine representative maize cultivars released between 1973 and 2000 in C hina were investigated in a 2‐year field experiment under three N applications. The H ybrid‐ M aize model was used to simulate maize yield potential in the period from 1973 to 2011. During the past four decades, the total thermal time (growing degree days) increased whereas the total precipitation and sunshine hours decreased. This climate change led to a reduction of maize potential yield by an average of 12.9% across different hybrids. However, the potential yield of individual hybrids increased by 118.5 kg ha −1 yr −1 with increasing year of release. From 1973 to 2000, the use efficiency of sunshine hours, thermal time, and precipitation resources increased by 37%, 40%, and 41%, respectively. The late developed hybrids showed less reduction in yield potential in current climate conditions than old cultivars, indicating some adaptation to new conditions. Since the mid‐1990s, however, the yield impact of climate change exhibited little change, and even a slight worsening for new cultivars. Modern breeding increased ear fertility and grain‐filling rate, and delayed leaf senescence without modification in net photosynthetic rate. The trade‐off associated with delayed leaf senescence was decreased grain N concentration rather than increased plant N uptake, therefore N agronomic efficiency increased simultaneously. It is concluded that modern maize hybrids tolerate the climatic changes mainly by constitutively optimizing plant productivity. Maize breeding programs in the future should pay more attention to cope with the limiting climate factors specifically.

The role of maize root size in phosphorus uptake and productivity of maize/faba bean and maize/wheat intercropping systems - YiKai Zhang; FanJun Chen; Long Li; YanHua Chen; BingRan Liu; YuLing Zhou; LiXing Yuan; FuSuo Zhang; GuoHua Mi (Science China Life Sciences, 2012)

Mapping QTLs for root system architecture of maize (Zea mays L.) in the field at different developmental stages - Hongguang Cai; Fanjun Chen; Guohua Mi; Fusuo Zhang; Hans Peter Maurer; Wenxin Liu; Jochen C. Reif; Lixing Yuan (Theoretical and Applied Genetics, 2012)

Positive feedback between acidification and organic phosphate mineralization in the rhizosphere of maize (Zea mays L.) - Xiaodong Ding; Li Fu; Chenjia Liu; Fanjun Chen; Ellis Hoffland; Jianbo Shen; Fusuo Zhang; Gu Feng (Plant and Soil, 2011)

Root growth in response to nitrogen supply in Chinese maize hybrids released between 1973 and 2009 - QiuPing Wu; FanJun Chen; YanLing Chen; LiXing Yuan; FuSuo Zhang; GuoHua Mi (Science China Life Sciences, 2011)

Ideotype root architecture for efficient nitrogen acquisition by maize in intensive cropping systems - GuoHua Mi; FanJun Chen; QiuPing Wu; NingWei Lai; LiXing Yuan; FuSuo Zhang (Science China Life Sciences, 2010)

Interaction between genotypic difference and nitrogen management strategy in determining nitrogen use efficiency of summer maize - Zhenling Cui; Fusuo Zhang; Guohua Mi; Fanjun Chen; Fei Li; Xinping Chen; Junliang Li; Lifei Shi (Plant and Soil, 2009)

Mapping QTLs for root traits under different nitrate levels at the seedling stage in maize (Zea mays L.) - Jianchao Liu; Jiansheng Li; Fanjun Chen; Fusuo Zhang; Tianheng Ren; Zhongjuan Zhuang; Guohua Mi (Plant and Soil, 2008)

Possible Involvement of Cytokinin in Nitrate-mediated Root Growth in Maize - Qiuying Tian; Fanjun Chen; Fusuo Zhang; Guohua Mi (Plant and Soil, 2005)

Genetic Analysis of Maize Root Characteristics in Response to Low Nitrogen Stress - Liang Chun; Guohua Mi; Jiansheng Li; Fanjun Chen; Fusuo Zhang (Plant and Soil, 2005)